Implementasi Protokol Kesehatan COVID-19 di Klinik Gigi: Studi pada Sektor Pemerintah dan Swasta - Liasari, Ira; Priyambodo, Ardian; Jumriani; Nur Aida, Wanda; Alisa Apriani, Nur (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Coronavirus Disease 2019 (Covid-19) is a large family of viruses that can cause illnesses ranging from the common cold to respiratory infections. Healthcare workers are among the frontline responders in managing the coronavirus outbreak, especially when special protection is required due to the limited availability of personal protective equipment during the pandemic. The pandemic has had a negative impact on all aspects of health, including dental care. Although all professional groups are at high risk of contracting Covid-19, healthcare workers are the most vulnerable, particularly during procedures that can generate splashes or aerosols. This study aims to identify the preventive measures taken against Covid-19 transmission among healthcare workers in the Selayar Islands Regency, South Sulawesi. The research uses a cross-sectional design. Data collection was carried out through a survey using a questionnaire distributed via Google Forms. The data analysis technique used is descriptive. The results of the study show that both dentists and dental nurses in public health center and private clinics implement Covid-19 prevention measures and take more stringent actions before and after dental procedures in order to minimize the spread of Covid-19.